PKM UMA SARI DI DESA SIDAN KABUPATEN GIANYAR BALI - I Gusti Ayu Ratih Permata Dewi; Putu Yudha Asteria Putri; Luh Suariani (Jurnal Abdi Masyarakat, 2021)
Coconut shells or coconut shells may not be useful for most people, but craftsmen in Sidan Village, Gianyar District, Gianyar Regency, Bali can produce various kinds of tools for Hindu religious ceremonies. Coconut shell crafts are also widely used as souvenirs for tourists who come to Bali. The community service program is carried out in the trading business and the production of ceremonial tools from coconut shell "Uma Sari" which is located in Sidan Village, Gianyar District, Gianyar Regency, Bali Province. Uma Sari is a partner owned by I Wayan Lanus as well as a coconut shell craft maker / craftsman. Mr. I Wayan Lanus started pioneering his work in 2016. He has acquired this skill from generation to generation among his extended family. The basic contribution of this program is to increase production capacity, increase online marketing, increase the quality of human resources, increase turnover and company assets.